The Impact of Online Gambling on Students: Productivity and Financial Health - Muhammad Rhenz Nanda; Tuti Anggraini; Nuri Aslami (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2025)
This study aims to examine the impact of online gambling on the productivity and financial health of college students in Medan. The rapid development of digital technology makes college students increasingly vulnerable to online gambling, which is often associated with negative impacts on social, financial, and academic aspects. This study used an associative quantitative technique with 100 students selected non-probabilistically. Data were collected using a structured questionnaire with a Likert scale and analyzed using simple regression in SPSS 25. The study found that online gambling negatively impacts productivity (β = -0.057; Sig. = 0.480) and financial health (β = -0.021; Sig. = 0.627). However, the impact was not statistically significant. These findings indicate that college students' awareness of financial risks, supported by religious and cultural norms, plays a role in mitigating the negative impacts of online gambling practices. However, online gambling still has the potential to cause real problems such as wastefulness, debt, and poor personal financial management. Therefore, it is recommended that universities and policymakers strengthen financial literacy programs and educate students about the dangers of online gambling to increase student resilience to digital gambling practices.Keywords: academic productivity, financial health, online gambling, risk awareness.